Panggung Komunitas dan Politik Kebersamaan: Refleksi Kohesi Sosial di Desa Karangwungulor - Ahmad Noval Romadhoni; Abd. Halim (JURNAL ILMIAH NUSANTARA, 2026)
This study aims to understand the community stage in Karangwungulor Village, which functions both as an arena of collective politics and as a means of strengthening social cohesion. Adopting a qualitative approach with an ethnographic method, the study explores cultural and political practices of the villagers, manifested through a series of collective activities that serve as the foundation of social cohesion. The findings reveal that collective politics in Karangwungulor arises from active community participation, not merely from formal village governance structures, but through the opening of local public spaces where diverse social elements come together to engage in dialogue and share roles in reinforcing social cohesion. Activities such as independence thanksgiving rituals, competitions, and carnivals are not only forms of entertainment but also media for fostering solidarity, trust, and collective identity. The phenomenon of collective politics is also evident in informal spaces, such as religious gatherings, coffee stalls, and youth forums. These local public spaces serve as arenas of negotiation in building social consensus. The dynamics of “front stage” and “back stage” communication among villagers illustrate that collective politics is fluid and flexible, blending formality with everyday familiarity. This study affirms that community-based collective politics can strengthen social cohesion, enhance citizens’ political awareness, and present an alternative model of local democracy that is participatory and inclusive. Nevertheless, challenges such as interest fragmentation, group dominance, and modernization need to be anticipated so that the community stage remains a solid foundation for sustaining the village’s social cohesion.